Non-Verbal Cues in Interactive Systems: Enhancing Proactivity through Winking and Turning Gestures - Siti Aisyah Binti Anas; Mazran bin Esro; Ahamed Fayeez bin Tuani Ibrahim; Yogan Jaya Kumar; Vigneswara Rao Gannapathy; Yona Falinie binti Abd Gaus; R. Sujatha (Advance Sustainable Science Engineering and Technology, 2025)
This investigation investigates the extent to which proactive behaviours in interactive objects—specifically animated eyes that exhibit behaviours such as blinking and turning—improve user interaction. Through a two-phase process, we investigate the influence of these behaviors on users’ perceptions of proactivity in both physical and virtual environments. In Phase I, we conducted a real-world study using a tangible box with animated eyes to evaluate user responses to expressive behaviours in single- and multi-person interactions. The results indicate that blinking significantly improves perceptions of the box’s intentionality and engagement, thereby fostering a more robust sense of proactivity. Phase II expands this investigation to a virtual environment, where 240 participants on Amazon Mechanical Turk (MTurk) participated, thereby validating the real-world findings. The online study confirms that perceived proactivity is consistently increased across contexts by blinking and turning. These findings indicate that integrating basic, human-like behaviors into interactive systems can enhance user engagement and provide practical advice for the development of sustainable, low-complexity interactive technologies. These discoveries facilitate the future development of resource-efficient and accessible human-computer interaction and robotic systems by simulating intentionality through minimal behavior.